Educação Financeira: uma proposta didática em sala de aula com o uso de planilhas eletrônicas - Couto, Andrey Alves do (2024)
The financial education involves the entire process of seeking, understanding, and applying everyday ideas related to the fundamental principles of financial mathematics, economics, and finance. This qualitative, documentary, and field study details and report an experience with third-year high school students from a school in Goiás, aiming to understand their prior knowledge of financial education concepts and their understanding and evolution after participating in the applied field activities. The core objective was for the research participants to familiarize themselves with fundamental concepts of financial mathematics, economics, and finance, such as assets and liabilities, cash flow, expense control, percentage and discounts, and ideas related to loans and investments. Additionally, the aim was to engage with these concepts through the systematic use of spreadsheets, a software that facilitates the understanding of these contents. Teaching financial with spreadsheets demonstrated effectiveness in students' understanding, as observed in the analysis of the final questionnaires and task completion analysis. Thus, the essential factor of integrating financial education into basic education is evident, as a vital role, fostering critical thinking and aiding in daily decision-making on personal and collective finances.